Nomenclatural notes on Brazilian Celtis (Cannabaceae) - Zamengo, Henrique Borges; Chamorro, Debora; Gaglioti, André Luiz; Oakley, Luis; Pederneiras, Leandro Cardoso (Phytotaxa, 2023)
In preparation for a new Neotropical taxonomic review and a global phylogeny focusing on the Neotropical lineages of Celtis, some nomenclatural changes are needed. Lectotypes are designated for Celtis alnifolia, C. asperula, C. brasiliensis, C. clausseniana, C. diffusa, C. morifolia, C. fluminensis, C. glycycarpa, C. hilariana, C. membranacea, C. orthacanthos, C. selloviana and Momisia integrifolia, and an epitype is designated for Celtis asperula. Celtis flavovenarum was proposed as a new name to replace the homonym C. morifolia. For C. spinosa we provide the locality of its type.